KOSAKATA EMOSI DALAM BAHASA DAYAK PERUAN DI DESA PERUAN DALAM KECAMATAN TAYAN HULU KABUPATEN SANGGAU - Yulia Damayanti; Hotma Simanjuntak; Ahmad Rabi’ul Muzammil (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to inventory the emotion vocabulary data, know the form of theword, know the meaning of the emotive, knowing denotative and implementing thelesson plan in grade 8 junior high school curriculum 2013 odd semester. Theresearch method used in this research is descriptive method with the form ofqualitative research. As for the data source in this study is the language of theDayak Peruan which is spoken by native speakers of the Dayak Peruan language inthe Peruan Dalam village, Tayan Hulu sub-district, Sanggau district thatrepresented by two informants. The technique used is are interview technique, note-taking technique, recordind technique and inducement technique. As for the tools theresearchers used were voice recording devices, questionnaires, notebook, and pens.This study obtained 35 emotion vocabularies in the Dayak Peruan language. Theform of the word used in the Dayak Peruan language is a single word totaling 14lexemes, there are 8 lexemes of affixed words, 1 lexeme of reduplication, 2 lexemesof compound words, and 10 lexemes of phrases. Based on denotative meaningcontained in the emotion vocabulary in the Dayak Peruan language, there are 25kexemes.Keywords: Dayak Peruan, Emotion vocabulary, Word form